The Blackwell companion to law and society - Sarat, Austin (Malden, Massachusetts Blackwell Pub., 2004)
The Blackwell Companion to Law and Society is an authoritative study of the relationship between law and social interaction. Thirty-two original essays by an international group of expert scholars examine a wide range of critical questions. Authors represent various theoretical, methodological, and political commitments, creating the first truly global overview of the field.

• Examines the relationship between law and social interactions in thirty-three original essay by international experts in the field.
• Reflects the world-wide significance of North American law and society scholarship.
• Addresses classical areas and new themes in law and society research, including: the gap between law on the books and law in action; the complexity of institutional processes; the significance of new media; and the intersections of law and identity.
• Engages the exciting work now being done in England, Europe, Australia, and New Zealand, South Africa, Israel, as well as "Third World" scholarship.
Includes index.
Keywords: Law -- Social aspects